Implementation of Servant Leadership at “X” Christian High School in Surabaya - Kristina Pujiastutianingsih; Ricky Ricky (Master of Management, School of Business and Management, Petra Christian University, 2023)
Servant leadership is a leadership approach that requires leaders to understand and meet their followers’ needs. During the pandemic, the learning process occurred remotely, requiring educational leadership that understands the difficulties faced by both teachers and students. This study examines how leaders and teachers understand and implement servant leadership in the learning process through a consultative project involving leaders, teachers, and students through interviews and questionnaires. The author used the Servant Leadership Behaviour Scale (SLBS) as a theoretical basis and statement items for 246 students. This research used ’mixed methods’ by combining qualitative and quantitative data. The author found the understanding of Servant Leadership in the leaders and teachers, including listening, serving by example, empathising, and cooperating to achieve common goals. Then, its application included listening, serving what’s needed, building relationships, inviting followers to think about the organisation, sparing time, paying attention to spirituality and morality, accepting criticism, and admitting mistakes. The SLBS dimensions found from those understanding are Voluntary Subordination, Covenantal Relationship, and Transforming Influence. The SLBS dimensions found from the application are Voluntary Subordination, Covenantal Relationship, Transforming Influence, Transcendence Spirituality, and Authentic Self.